2019
DOI: 10.1177/2325967119865866
|View full text |Cite
|
Sign up to set email alerts
|

Time-Loss Injuries in Karate: A Prospective Cohort Study of 4 Consecutive World Karate Championships

Abstract: Background: Prospective studies on injuries in martial arts competitions are scarce, especially those involving time-loss injuries. The upsurge of karate athletes competing in top-level karate competitions warrants elucidation of the time-loss injury risk. Purpose: To determine the time-loss injury proportion and incidence rate, describe the injury pattern among elite senior karate athletes, and compare the risk of time-loss injuries in male versus female athletes and in individual (ie, weight categories) vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
(24 reference statements)
0
6
0
1
Order By: Relevance
“…Given the potential for injury from striking impacts, protective equipment has been made mandatory in some disciplines involving kicking strikes [ 129 , 130 ]. Despite this, injury prevalence research has indicated that only a limited proportion of participants (26.15%) reported using protective equipment during training sessions in which injury occurred [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the potential for injury from striking impacts, protective equipment has been made mandatory in some disciplines involving kicking strikes [ 129 , 130 ]. Despite this, injury prevalence research has indicated that only a limited proportion of participants (26.15%) reported using protective equipment during training sessions in which injury occurred [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Karate merupakan salah satu cabang olahraga beladiri body contact, dimana dalam pelaksanaan pertandingannya dilakukan dengan intensitas tinggi serta sangat rentan dengan terjadinya cedera (Augustovičová et al, 2019) (Pal et al, 2020). Kondisi ini pada gilirannya menuntut para atlet agar dapat mempersiapkan diri dengan sebaik-baiknya.…”
Section: Pendahuluanunclassified
“…Numerous examples of research are available on the injury prevalence in various combat sports such as wrestling [ 25 , 26 , 27 , 28 ], judo [ 29 , 30 , 31 ], taekwondo [ 32 , 33 , 34 , 35 , 36 , 37 ], boxing [ 38 , 39 , 40 , 41 , 42 ], and karate [ 43 , 44 , 45 ], as well as comparisons of injury prevalence among Olympic combat sports [ 2 , 46 , 47 , 48 ] and martial arts [ 1 , 49 ]. Due to the heterogeneity of these studies in terms of participants (e.g., elite vs. amateur, children or adolescents vs. adults, and male vs. female), injury definitions, surveillance methods (e.g., self-reporting, medical records, and injury surveillance systems), and characteristics of the reported injuries (e.g., competition injuries vs. training injuries and acute vs. chronic injuries), it is difficult to get an overall view of the injury rate, type, location, and severity.…”
Section: Injuries In Combat Sportsmentioning
confidence: 99%
“…However, the greatest injury burden risk was found in judo when both the incidence and severity were taken into consideration [ 2 ]. The incidence rate for time-loss injuries in top-level karate athletes was reported to be relatively low (10%) based on the data collected at four consecutive World Karate Championships (2010, 2012, 2014, and 2016), and these injuries were due to fractures (41%), dislocations (20%), or concussions (12%) [ 44 ].…”
Section: Injuries In Combat Sportsmentioning
confidence: 99%